Paradigma Kognitif dalam Pembelajaran melalui Filsafat Ilmu - Erdyna Dwi Etika; Siti Masitoh; Mochamad Nursalim (Departement of Mathematics Education, 2023)
Educators need to understand the developmental stages of students. One of the developments is cognitive development. Philosophy of science is important in cognitive learning studies to produce a more comprehensive understanding. This literature review aims to: (1) describe cognitive studies according to experts, (2) describe cognitive theory in terms of philosophy of science and (3) describe the implementation of cognitive studies in learning. The results of the study: (1) Cognitive Theory according to theorists such as Piaget (1964), Vygotsky (1978), Lewin (1935, 1936), and Brunner (1956) states that (a) all individuals develop in the same way, although the styles and stages are different; (b) cognitive abilities resulting from cultural and social interaction; (c) each individual is in a psychological force field where the place to react is called the field of life; and (d) learning can create conditions that allow individuals to learn more about themselves; (2) The ontological understanding of cognitive development theory is the existence of developmental processes in determining human understanding and acquisition of knowledge. The epistemological review of cognitive development theory lies in the search for truth and understanding through empirical investigation, logical inference, and systematic exploration of how individuals learn and grow cognitively over time. Axiological review of cognitive development theory lies in the commitment to foster ethical behavior and create a learning environment through the acquisition and application of knowledge about cognitive growth and learning; and (3) Cognitive Theory can be implemented in learning, namely through learning strategies.